Technology-intensive firms in the transition to a new energy paradigm: Commercialization strategies, alliances and networks - Salavisa, I.; Salavisa, I.; Sousa, C. (2nd International Conference Governance of a Complex World, Innovation and Cooperation as Entrepreneurial Challenges, 2013)
This paper focuses on the behaviour of new technology-intensive firms (NTIFs) in the process of developing research-based renewable energy technologies, and introducing them into the market. Our main assumption is that the introduction of new energy technologies is closely connected with the creation of a variety of small technology-intensive firms that are the conveyors of these technologies and act as challengers to the statu quo. We adopt a business model framework to study value creation and value capture by NTIFs, taking into account the context, where policy options, obstacles and opportunities impact the action and outcomes of the companies. The framework is applied to a group of 28 Portuguese NTIFs in several renewable energy areas.